Consumer Discrimination; Bias towards Customers in the Service Industry - Fayola Maharani; Kimberly Phwa; Tri Wismiarsi (Magister Manajemen - Universitas Sultan Ageng Tirtaysa, 2022)
Consumer racial profiling, a phenomenon often described as bias behaviors towards customers directed by employees, is often overlooked by companies during employee training stages. The lack of research regarding this topic has caused a rift in customer service towards consumers who are of minor ethnic backgrounds. Diversity training is one of the ways that companies have chosen as a solution to reduce consumer racial profiling by the workforce. The purpose of this research is to identify the effectiveness of workforce diversity training towards consumer racial profiling. The data required for this research was collected via a survey questionnaire that was measured using a quantitative scale composed of six scales. The data analysis, shows that the impact of diversity training on employees’ behaviors towards customers is not as significant as hypothesized, meaning that companies would need to reach out for other solutions in order to counter consumer racial profiling.